1994
DOI: 10.1128/jb.176.23.7383-7386.1994
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lysyl-tRNA synthetase expression by histone-like protein H-NS of Escherichia coli

Abstract: The lysU gene encoding lysyl-tRNA synthetase of Escherichia coli is normally silent at low temperatures and is expressed by certain metabolites and stimuli. A novel class of lysU-constitutive mutations were isolated by random insertion mutagenesis. These mutations nullified the hns gene encoding a histone-like protein, H-NS, and affected thermoregulation of lysU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The rationale for undertaking such an inter-kingdom protein substitution was based on the following considerations: (i) H-NS regulates the expression of several genes in Escherichia and Salmonella (Higgins et al, 1990;Dorman, 1991); (ii) many H-NS-regulated genes have curved promoter regions Dersch et al, 1993;Ito et al, 1994) note that we have shown here that the bgl regulatory region contains curved DNA; (iii) H-NS acts as a transcriptional regulator by binding to curved DNA (Owen-Hughes et al, 1992;; (iv) Btcd binds tightly to curved DNA (Mazin et al, 1994a,b), as does H-NS (Yamada et al, 1990;Mizuno, 1992); and (v) mammalian proteins involved in DNA and RNA transactions have been found to substitute for their E.coli prototypes (Kodama et al, 1991;O'Connor and Laval, 1991;Sweasy and Loeb, 1992;Sakumi etal., 1993;Kim and Loeb, 1995). Not all of H-NS functions can be replaced by Btcd functions Btcd does not fully substitute for H-NS.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for undertaking such an inter-kingdom protein substitution was based on the following considerations: (i) H-NS regulates the expression of several genes in Escherichia and Salmonella (Higgins et al, 1990;Dorman, 1991); (ii) many H-NS-regulated genes have curved promoter regions Dersch et al, 1993;Ito et al, 1994) note that we have shown here that the bgl regulatory region contains curved DNA; (iii) H-NS acts as a transcriptional regulator by binding to curved DNA (Owen-Hughes et al, 1992;; (iv) Btcd binds tightly to curved DNA (Mazin et al, 1994a,b), as does H-NS (Yamada et al, 1990;Mizuno, 1992); and (v) mammalian proteins involved in DNA and RNA transactions have been found to substitute for their E.coli prototypes (Kodama et al, 1991;O'Connor and Laval, 1991;Sweasy and Loeb, 1992;Sakumi etal., 1993;Kim and Loeb, 1995). Not all of H-NS functions can be replaced by Btcd functions Btcd does not fully substitute for H-NS.…”
Section: Discussionmentioning
confidence: 99%
“…H-NS prevents the transcription of rRNA by binding to the rrn promoter (47). It also regulates negatively lysU, which codes for lysyl-tRNA synthetase (14). The growth temperature is an important environmental determinant regulating the expression of hns.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal replacements of ApaH (open reading frame only) with yeast Apa2, a stabilized ApaH variant (ApaH_D7), and ApaH mutants with impaired enzymatic activity. LysU's expression is thought to be triggered by heat stress, and it has thus been suggested to act primarily as an Ap4A synthetase [38,39]. significantly reduced -≤ 0.02 lM compared to 0.2 lM in the wild-type (Table 1), yet within the perturbation range expected for a signaling molecule.…”
Section: Regulation Of Apahmentioning
confidence: 99%